Workplace, Work Motivation, and Implementation of Guidance and Counselling Service in Secondary School - Muh. Mansyur Thalib; Ridwan Syahran (Universitas Tadulako, 2020)
The main problem of this research is how relationship between workplace, work motivation, and implementation of guidance and counseling service. The research intended to identify and describe the relationship between workplace, work motivation, and implementation of guidance and counseling service. There were three variable in this research, is: workplace, work motivation, and implementation of guidance and counseling service. The samples on this research were 60 guidance teachers in secondary school. The data collected by having questionnaire. The data was analyzed in descriptive and inferentially. Descriptive analysis was frequency distribution and percentage. Inferential analysis intended to test the research hypothesis with single regression analysis and multiple regression analysis. The research showed that there were 36,66% of guidance teachers had support classification on workplace, there ware 35.00% of guidance teachers had high classfication on work motivation, and there were 33,33% of guidance teachers had high classification on implementation of guidance and counseling service. The conclusion of the hypothesis testing were a) there was a positive relationship between workplace and implementation of guidance and counseling service, b) there was a positive relationship between work motivation and implementation of guidance and counseling service, and c) there was a positive relationship between workplace and work motivation simultantly with implementation of guidance and counseling service.